CONSUMER PROFILE OF MARGARIN BLUE BAND IN PONTIANAK - Marcela, Sintia; Kusrini, Novira; Maswadi, Maswadi (Jurnal Sains Mahasiswa Pertanian, 2019)
This research is based on the increasing number of margarine producers in Indonesia. Blue band is one of the dominant margarine brand in Indonesia market. This is evident from the existence of the blue band that does not fade although other brands come to dominate and become competitors. Consumer loyalty that until now still retain the blue band market. The purpose of this study is to determine the factors that effect the loyalty of margarine blue band consumers in Pontianak city. The population in this study were consumers who consumed margarine blue band in Pontianak city, with the number of respondents as many as 100 people. The analysis used is factor analysis. The result of this research is there are 5 factors from 7 factors influencing custumer loyalty margarine blue band.Â Keyword: factor analys, blue band, consumer loyalty